2022
DOI: 10.3389/fphar.2022.977370
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CYP450 and drug transporter mediated by gut microbiota under high-altitude hypoxia

Abstract: Hypoxia, an essential feature of high-altitude environments, has a significant effect on drug metabolism. The hypoxia–gut microbiota–CYP450/drug transporter axis is emerging as a vital factor in drug metabolism. However, the mechanisms through which the gut microbiota mediates the regulation of CYP450/drug transporters under high-altitude hypoxia have not been well defined. In this study, we investigated the mechanisms underlying gut microbial changes in response to hypoxia. We compared 16S ribosomal RNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…For example, they both participate in the regulation of bile acid metabolism. PXR has important downstream factors in the liver cytochrome P450 3A4(CYP3A4, Cyp3a11 in mice) and cytochrome P450 17A1 (Cyp17a1), which are key metabolic enzymes in the body 30,31 . PXR initiates CYP3A4 transcription and alters the metabolic rate by binding to specific ligands, such as some drugs 10,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they both participate in the regulation of bile acid metabolism. PXR has important downstream factors in the liver cytochrome P450 3A4(CYP3A4, Cyp3a11 in mice) and cytochrome P450 17A1 (Cyp17a1), which are key metabolic enzymes in the body 30,31 . PXR initiates CYP3A4 transcription and alters the metabolic rate by binding to specific ligands, such as some drugs 10,32,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…PXR has important downstream factors in the liver cytochrome P450 3A4(CYP3A4, Cyp3a11 in mice) and cytochrome P450 17A1 (Cyp17a1), which are key metabolic enzymes in the body. 30,31 PXR initiates CYP3A4 transcription and alters the metabolic rate by binding to specific ligands, such as some drugs. 10,32,33,34 Previous studies in our laboratory have found that PXR regulates Cyp17a1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current study ignores the role of drug metabolism on bioavailability. Previous studies have demonstrated the capacity for the gut microbiome to modulate hepatic cytochrome P450 (CYP450) enzyme activities [41,42]. In the context of lurasidone, this presents another avenue of pharmacokinetic modulation as lurasidone is extensively metabolised (through oxidative N-dealkylation between the piperazine and cyclohexane rings) by CYP450, forming lurasidone metabolites 14326, 14283 (both active) and 20219, 20220 (inactive) [43].…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…of escitalopram responders and non-responders (C57BL/6 male mice model, n: 7/group, mean age: 4-6 weeks)45 . Furthermore, the gut microbiome has shown capacity to modulate hepatic cytochrome P450 (CYP450) characteristics as explored by Wang et al and Bai et al46,47 . In the context of lurasidone, it presents another avenue of pharmacokinetic modulation as lurasidone is extensively metabolised (thought oxidative N-dealkylation between the piperazine and cyclohexane rings) by CYP450, forming lurasidone metabolites 14326, 14283…”
mentioning
confidence: 99%